Thermally conductive composite film filled with highly dispersed graphene nanoplatelets via solvent-free one-step fabrication - Yu, Jaesang; Cha, Ji Eun; Kim, Seong Yun (ELSEVIER SCI LTD, 2017)
We proposed a solvent-free melting process for fabricating high-conductivity polymer composite films filled with highly dispersed GNP fillers. The excellent dispersion of GNP fillers in the composite films was observed using X-ray micro-computed tomography (micro-CT), a non-destructive three-dimensional (3D) analysis technique that helps to analyze the internal structures of composite films with precision. The excellent dispersion of GNP fillers also confirmed by the fact that experimentally determined electrical and thermal conductivity values of the composite films were well consistent with the theoretical calculations obtained with a Mod-Tanaka method. The composite films exhibited an electrical conductivity on the order of 10(1) S/m and the in-plane thermal conductivity of 7.1 W/m.K when they contained 20 wt% GNP fillers. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: CARBON-NANOTUBE COMPOSITES; POLYMER COMPOSITES; EDDY-CURRENT; THERMOPLASTIC COMPOSITES; SYNERGISTIC IMPROVEMENT; ELECTRICAL PERCOLATION; THEORETICAL APPROACH; ENHANCED DISPERSION; HEAT-FLOW; FIBER